New Trends in Rewards Allocation Preferences: A Sino-U.S. Comparison - Chen, Chao C. (Academy of Management Journal, 1995)
This study explored situations in which current organizational goal priorities require rewards allocation logics that contradict traditional distributive norms and the natural characteristics of resources. Data from Chinese and U.S. business organizations showed that the Chinese employees were economically oriented and preferred to invoke differential rules (those that result in unequal distribution of rewards) for the allocation of both material and socioemotional rewards whereas their U.S. counterparts were humanistically oriented and preferred a performance rule for the allocation of material rewards but equality rules for socioemotional rewards. The results are discussed in the light of organizational goal priorities, cultural traditions, and other sociohistorical factors.